2010
DOI: 10.3109/13550281003682547
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus–induced apoptosis in MeWo cells is accompanied by down-regulation of Bcl-2 expression

Abstract: Varicella-zoster virus infects multiple human and monkey cells in culture. The mode of cell death appears to be autophagy or apoptosis. Analysis of VZV-infected human melanoma (MeWo) cells revealed that Bcl-2 mRNA and protein levels were decreased significantly 64 and 72 hpi (hours post infection), accompanied by the release of cytochrome c from mitochondria into the cytoplasm. Western blot analysis of virus-infected cells revealed activation of caspase-8, a marker for the extrinsic pathway of apoptosis, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…Apoptosis was reported 24 to 48 h after VZV infection of fibroblasts (7), 48 h after infection of T cells (25), 64 to 72 h after infection in MeWo cells (1), and 72 to 96 h after infection of Vero cells (24). We found that ORF12 protein inhibited apoptosis of VZV-infected MeWo cells early (Յ30 h) after infection.…”
Section: Discussionmentioning
confidence: 59%
“…Apoptosis was reported 24 to 48 h after VZV infection of fibroblasts (7), 48 h after infection of T cells (25), 64 to 72 h after infection in MeWo cells (1), and 72 to 96 h after infection of Vero cells (24). We found that ORF12 protein inhibited apoptosis of VZV-infected MeWo cells early (Յ30 h) after infection.…”
Section: Discussionmentioning
confidence: 59%
“…Equimolar concentrations of all four HSV-1 isomers are packaged into the virion (Roizman, 1979), whilst only two isomers (both U S inversions) predominate in packaged VZV (Kinchington et al, 1985). The drastic reduction of U L inversions in VZV DNA within infectious virus particles is attributed to a DNA sequence uniquely located at the extreme left-end of the virus U L DNA that is responsible for cleavage of genome-size DNA during packaging (Kaufer et al, 2010). As this sequence is not present at the extreme right-end of VZV U L DNA, the single cleavage site does not permit U L inversions to be packaged into infectious virus particles.…”
Section: Introductionmentioning
confidence: 99%
“…At the single-cell level, the VZV lytic replication cycle culminates in 9-12 h (Reichelt et al, 2009), but it can take 3-5 days for the entire culture to show extensive VZV-induced syncytia (Grose & Brunel, 1978) and cell death either by lysis or apoptosis (Brazeau et al, 2010;Pugazhenthi et al, 2011). Whilst cell-free VZV preparations have been reported, virus yield remains extremely low: 10 5 p.f.u.…”
Section: Introductionmentioning
confidence: 99%
“…3). All 68 VZV genes are transcribed during productive virus infection in tissue culture cells [32] where virus spreads from cell to cell, resulting in extensive cytopathologic effects and apoptotic cell death in 3–5 days [33]. However, during latency VZV transcription is limited, no cytopathologic effects are evident, and production of infectious virions is inhibited.…”
Section: Vzv Latencymentioning
confidence: 99%